شبهات حول المرأة فى السنة : دراسة لمناذج مختارة والرد عليها فى ضوء السنة الشريفة - روضة الفردوس بنت فتح ياسين (al-Jami'ah al-Islamiyah al-'Alamiyah bi-Maliziya, 2006)
This research is a study on selected hadith regarding women which literally sound suspicious (syubhat) in order to answer them according to God's revelation and women psychology. It begins by discovering the development of distrust in hadith and its rank within the Islamic legislation. Other issue related is the dubious hadith raised regarding Ummahatul Mukminin (The Mother of Believers) and the answers for every dubious aspect. This study adopts an inductive method to search and gain all kinds of suspicious raised, recount the hadith to the sources, apprehends scholar's interpretations and investigates women's psychological aspects. It also adopts the analytical method to explain these hadith and compare them with the Qur'anic verses, recount the Prophet's PBUH explanation of women nature and the expected treatment towards them. This research comes to the conclusion that the truth is; there's no suspicious point at all if the hadith contemplated with deep understanding. It also identified the method used by hadith deniers in rising dubious; by comparing two or more authentic hadith and presents them as contradicting each other, or by confusing the status of the Sahabah (companions) and Ummahatul Mukminin, or by claiming the hadith as disregarding the principles of equality and women rights.